2007
DOI: 10.1507/endocrj.k06-156
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23 (FGF23) in Patients with Transient Hypoparathyroidism: Its Important Role in Serum Phosphate Regulation

Abstract: Abstract. Hypoparathyroidism is a complication of thyroidectomy that causes hyperphosphatemia primarily due to enhanced reabsorption of phosphate in the kidney resulting from decreased parathyroid hormone (PTH) secretion. Fibroblast growth factor-23 (FGF23) is a hormone-like factor that is thought to play an important role in phosphate homeostasis. However, the changes and role of FGF23 in transient hypoparathyroidism after thyroidectomy are not clear. We examined changes in serum levels of calcium, phosphate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
2
17
1
1
Order By: Relevance
“…These observations are consistent with emerging evidence for a complex regulatory mechanism for FGF23 secretion that involves PTH (Silver and Naveh-Many 2012) as well as serum concentrations of calcium and phosphorus to ensure a normal calcium × phosphorus product (Quinn et al 2013). By contrast, previous studies of patients with chronic (Gupta et al 2004) or acute and transient hypoparathyroidism (Yamashita et al 2007) had shown that levels of serum FGF23 were increased, and were correlated with hyperphosphatemia. But in these cases the patients were also receiving calcitriol or 1α-hydroxyvitamin D, which would increase FGF23 (Collins et al 2005; Gupta et al 2004).…”
Section: Discussionmentioning
confidence: 62%
“…These observations are consistent with emerging evidence for a complex regulatory mechanism for FGF23 secretion that involves PTH (Silver and Naveh-Many 2012) as well as serum concentrations of calcium and phosphorus to ensure a normal calcium × phosphorus product (Quinn et al 2013). By contrast, previous studies of patients with chronic (Gupta et al 2004) or acute and transient hypoparathyroidism (Yamashita et al 2007) had shown that levels of serum FGF23 were increased, and were correlated with hyperphosphatemia. But in these cases the patients were also receiving calcitriol or 1α-hydroxyvitamin D, which would increase FGF23 (Collins et al 2005; Gupta et al 2004).…”
Section: Discussionmentioning
confidence: 62%
“…The median serum PTH level was 6.0 pmol/l (4.00–9.00) and 25 out of 51 (49%) toddlers had PTH above the upper end of the reference range value of 6.4 pmol/l. At the start of the trial in September 2006, the mean (SD) serum 25(OH)D concentration for the whole group was 126.3 (SD 62.6) nmol/l, indicating that the subjects had good body stores of vitamin D. For the whole group, the median FGF-23 level was 9.1 ng/l (5–14.2), which is just below the adult reference range of 10–50 nmol/l 19. Serum FGF-23 concentration was not related to serum phosphorus concentration.…”
Section: Resultsmentioning
confidence: 89%
“…Dietary/serum calcium regulates FGF23 production (Figure 3), whereas serum calcium may alter renal phosphate excretion (74). Although FGF23 levels rise after transient hypoparathyroidism, the level achieved is insufficient to correct the serum phosphorus (75). This "inadequate" FGF23 response may be protective because a more robust rise in FGF23 could further suppress 1,25(OH)D and PTH production, Figure 4.…”
Section: Other Potential Phosphatonin/minhibins In Xlhmentioning
confidence: 99%